2023
DOI: 10.1039/d3dt00318c
|View full text |Cite
|
Sign up to set email alerts
|

General synthesis of CoCeMOx trimetallic oxides via a cation exchange reaction for the oxygen evolution reaction

Abstract: Cobalt-based spinel oxides are considered as potential candidates for oxygen evolution reaction (OER) due to their abundant valence changes and promising electrochemical activity, but low intrinsic activity hinders their practical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…When the reaction was extended to 3–6 h, the CoFe-SUCS structure remained almost the same morphology of the sea urchin-like hollow core–shell nanosphere, which is completely different from that of Co-CDSAAs (Figures f–i and S2f–i). Fourier transform infrared (FT-IR) spectroscopy (Figure S3) revealed that their characteristic absorption peaks are almost the same except for the infrared absorption peaks in the fingerprint region, which is different from our report. This may be the reason for the different morphologies of the CoFe-SUCS and Co-CDSAAs.…”
Section: Resultscontrasting
confidence: 82%
See 4 more Smart Citations
“…When the reaction was extended to 3–6 h, the CoFe-SUCS structure remained almost the same morphology of the sea urchin-like hollow core–shell nanosphere, which is completely different from that of Co-CDSAAs (Figures f–i and S2f–i). Fourier transform infrared (FT-IR) spectroscopy (Figure S3) revealed that their characteristic absorption peaks are almost the same except for the infrared absorption peaks in the fingerprint region, which is different from our report. This may be the reason for the different morphologies of the CoFe-SUCS and Co-CDSAAs.…”
Section: Resultscontrasting
confidence: 82%
“…It is evident that the Co species changes to multiple valence states from Co 2+ after CoFe-SUCS was calcined in an Ar/H 2 atmosphere (Figures b and S10a). In the Co 2p spectrum (Figure b), with the presence of satellite peaks at 802.7, 798.8, 786.8, and 785.1 eV, the Co 3+ and Co 2+ fitted peaks of Co 2p 3/2 located at 779.7 and 782.3 eV respectively, and the peaks located at 794.4 and 795.5 eV fitted Co 2p 1/2 orbital, except that a new small signal of Co mental was detected, which confirmed the part reduction process in Ar/H 2 atmosphere. , As for Fe 2p orbital regions (Figure c), the spectra show peaks located at 711.3 and 709.6 eV correspond to Fe 3+ and Fe 2+ of Fe 2p 3/2 orbital, respectively. The reason for the number of fitted peaks in BN-Fe 3 O 4 /CoO x being more than that in CoFe-SUCS could be this: the Co element in CoFe-SUCS assembled through the coordination of Co 2+ with the organic ligand HL 10 resulted in the presence of the fitted peaks of Co 2+ . After the calcination in the reducing gas Ar/H 2 , some Co 2+ is reduced to Co 0 , and the O element in the organic ligand HL 10 can partially oxidize Co 2+ to Co 3+ during the pyrolysis process.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations